The influence of surfaces and interfaces on high spatial resolution vibrational EELS from SiO2. (1st February 2018) - Venkatraman, Kartik; Rez, Peter; March, Katia; Crozier, Peter A
Abstract: High-resolution monochromated electron energy-loss spectroscopy has the potential to map vibrational modes at nanometer resolution. Using the SiO2 /Si interface as a test case, we observe an initial drop in the SiO2 vibrational signal when the electron probe is 200 nm from the Si due to long-range nature of the Coulomb interaction. However, the distance from the interface at which the SiO2 integrated signal intensity drops to half its maximum value is 5 nm. We show that nanometer resolution is possible when selecting the SiO2 /Si interface signal which is at a different energy position than the bulk signal. Calculations also show that, at 60 kV, the signal in the SiO2 can be treated non-relativistically (no retardation) while the signal in the Si, not surprisingly, is dominated by relativistic effects. For typical transmission electron microscope specimen thicknesses, surface coupling effects must also be considered.